2011
DOI: 10.1177/1350650110397460
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-Hydrodynamic Couplestress Squeeze Film Lubrication of Circular Stepped Plates

Abstract: The theoretical analysis of the effect of transverse magnetic field on the couplestress squeeze film lubrication between circular stepped plates is presented. The modified Reynolds equation is derived. The closed-form expressions are obtained for the squeeze film pressure, load-carrying capacity, and squeeze film time. The squeeze film characteristics are presented for different operating parameters. It is observed that the effect of applied magnetic field on the squeeze film lubrication between circular stepp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…The fluid film thickness, h , is defined by h=h1 for 0rKR=h2 for KRrR with 0K1. The modified Reynolds equation for the MHD couple‐stress squeeze film between smooth circular stepped plates derived by Naduvinamani et al . is 1rrS(H,l,B0)rpr=σB02V,where S(H,l,B0)=2l(A2B2)B2AtanhAH2lA2BtanhBH2l+H. A={}1+()14l2σB02/μtrue12212,B={}1()14l2σB02/μtrue12212.…”
Section: Mathematical Formulation Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluid film thickness, h , is defined by h=h1 for 0rKR=h2 for KRrR with 0K1. The modified Reynolds equation for the MHD couple‐stress squeeze film between smooth circular stepped plates derived by Naduvinamani et al . is 1rrS(H,l,B0)rpr=σB02V,where S(H,l,B0)=2l(A2B2)B2AtanhAH2lA2BtanhBH2l+H. A={}1+()14l2σB02/μtrue12212,B={}1()14l2σB02/μtrue12212.…”
Section: Mathematical Formulation Of the Problemmentioning
confidence: 99%
“…Hence, in this paper, an attempt has been made to study the combined effect of surface roughness and MHD on the couple‐stress squeeze film characteristics between circular stepped plates. The results are compared with the smooth case studied by Naduvinamani et al …”
Section: Introductionmentioning
confidence: 99%
“…The combined effects of couple stress and MHD on bearing characteristics are studied by Das [13], circular stepped plates by Naduvinamani et al [14] and different types of finite plates by Fathima et al [15]. The results obtained in these studies showed an increase in load carrying capacity of bearings as the strength of applied magnetic field increases and also with increase in the value of couple stress parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have applied the hydromagnetic flow model and Stokes couple stress model to engineering problems. For example, Lin, et al (22), Naduvinamani, et al (23), and Ramesh Kudenatti, et al (24) have shown that the effect of applied magnetic field is more significant in increasing the load-carrying capacity and squeeze film time. Fathima,et al (25) have studied the combined effects of couple stresses and magnetic field in anisotropic plates.…”
Section: Introductionmentioning
confidence: 99%